Effect Of Progressive Muscle Relaxation Therapy And Slow Deep Breathing On Blood Pressure Of Elderly With Hypertension - Hasina, Siti Nur; Rahmadaniar Aditya Putri; Ratna Yunita Sari; Riska Rohmawati; Imamatul Faizah (Journal for Quality in Public Health, 2024)
Hypertension is one of the degenerative diseases that often appear in the elderly. This starts with a person's inability to control or maintain a stable condition of blood pressure in the body. The frequent visits of the elderly to the elderly Posyandu in Janti village with complaints and blood pressure above normal reflect the lack of efforts of the elderly in controlling or stabilizing blood pressure in the body. The aim of the study was to determine the effect of progressive muscle relaxation therapy andslow deep breathing on hypertension elderly blood pressure. Research design Like an experiment with a sample of 62 elderly people with hypertension, selected by purposive sampling technique which was then divided into 2 groups, 31 people in the treatment group were given a combination of progressive muscle relaxation andslow deep breathing, and 31 people in the control group were given therapyslow deep breathig. Data analysis used the Paired T-Test and Independent T-Test. The results of the study in the treatment group before being given the intervention obtained an average of 146.00 mmHg systolic, 91.52 mmHg diastolic (degree 1 hypertension). Independent T-Test analysis found on systolic and diastolic blood pressure, pulse value ρ = 0.000 < α = 0.05, meaning that there is a combination effect of progressive muscle relaxation and music therapy on blood pressure and pulse. Progressive muscle relaxation therapy and slow deep breathing can reduce blood pressure in elderly people with hypertension. It is hoped that this therapy can be used as a non-pharmacological therapy to help lower blood pressure in hypertensive patients in addition to using pharmacological therapy.